2021
DOI: 10.1093/cid/ciab311
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Seasonal Respiratory Illnesses in the United States During the Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: Background Respiratory tract infections are common, often seasonal, and caused by multiple pathogens. We assessed whether seasonal respiratory illness patterns changed during the COVID-19 pandemic. Methods We categorized emergency department (ED) visits reported to the National Syndromic Surveillance Program according to chief complaints and diagnosis codes, excluding visits with diagnosed SARS-CoV-2 infections. For each week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 20 publications
18
72
0
Order By: Relevance
“…According to other studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 ], our results show that the circulation of respiratory viruses was disrupted during the pandemic, even if the magnitude of this effect was different between the viruses analyzed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…According to other studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 ], our results show that the circulation of respiratory viruses was disrupted during the pandemic, even if the magnitude of this effect was different between the viruses analyzed.…”
Section: Discussionsupporting
confidence: 78%
“…These preventive strategies, in particular physical distancing and the use of masks, may have contributed to reducing the circulation of other respiratory viruses besides SARS-CoV-2 [ 12 , 13 ]. Different studies show that social restrictions had an impact on the spread of both seasonal influenza [ 14 , 15 , 16 , 17 , 18 ] and other respiratory viruses [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic, many countries have observed a near total disappearance of RSV and influenza cases. 3,4 In Canada, 339 627 tests for RSV were reported through the Centre for Immunization and Respiratory Infectious Diseases. Of these tests, 239 were positive between Aug. 29, 2020, and May 8, 2021.…”
mentioning
confidence: 99%
“…Recently, several researchers reported that the NPIs for COVID-19 suppressed the outbreak of common respiratory virus infections as well as that of COVID-19. 6 7 8 9 10 11 12 13 14 The outbreaks of common respiratory virus infections are not directly affected by the COVID-19 vaccination rate or the emergence of SARS-CoV-2 variants; hence, the data of common respiratory virus infection outbreaks help determine the effect of NPIs without being affected by other factors related to the COVID-19 outbreak. Among the common respiratory viruses, non-enveloped viruses such as rhinovirus (RV), human bocavirus (BOV), and adenovirus (ADV) are continuously detected despite the implementation of NPIs during the COVID-19 pandemic, because they are more resistant to environmental challenges or alcohol-based disinfectants than enveloped viruses and can be easily transmitted through not only respiratory droplets but also contacts with unwashed hands.…”
Section: Introductionmentioning
confidence: 99%